2005
DOI: 10.1111/j.1432-1033.1980.tb06152.x
|View full text |Cite
|
Sign up to set email alerts
|

The Assembly of Ribosomes in HeLa Cell Nucleoli

Abstract: The order in which ribosomal proteins become associated with nucleolar pre-rRNA was studied by measuring the kinetics of label accumulation in ribosomal proteins isolated from the cytoplasmic ribosomes, as well as by two-dimensional polyacrylamide gel electrophoresis of protein extracted from ribosome precursor particles. Tentative identifications of early-adding and late-adding groups of proteins have been made.The process by which ribosomes are assembled in growing HeLa cells has been studied by following th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
4

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 22 publications
0
12
0
4
Order By: Relevance
“…To address this possibility, we analyzed depletion of another essential r-protein, Rpl10 (uL16). Unlike Rpl17, Rpl10 is incorporated into nascent 60S subunits after their cytoplasmic export, as shown by previous studies in both mammalian cells (Auger-Buendia et al 1979;Lastick 1980) and yeast (Saveanu et al 2003;West et al 2005;Ohmayer et al 2013). Depletion of Rpl10 severely inhibited cell growth, as did depletion of Rpl17 (Fig.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…To address this possibility, we analyzed depletion of another essential r-protein, Rpl10 (uL16). Unlike Rpl17, Rpl10 is incorporated into nascent 60S subunits after their cytoplasmic export, as shown by previous studies in both mammalian cells (Auger-Buendia et al 1979;Lastick 1980) and yeast (Saveanu et al 2003;West et al 2005;Ohmayer et al 2013). Depletion of Rpl10 severely inhibited cell growth, as did depletion of Rpl17 (Fig.…”
Section: Resultsmentioning
confidence: 55%
“…Incorporation of r-proteins into preribosomes in vivo follows a broadly hierarchical order, according to which these proteins can be divided into several earlier-and later-acting assembly groups (Auger-Buendia et al 1979;Lastick 1980;Todorov et al 1983;O'Donohue et al 2010;Chen and Williamson 2013;Gamalinda et al 2014). Early-binding r-proteins promote subsequent assembly steps by facilitating structural rearrangements in pre-rRNA and enabling binding of assembly factors (Ferreira-Cerca et al 2007;Babiano and de la Cruz 2010;Jakob et al 2012;Ohmayer et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Seminal work done in yeast and HeLa cells suggested that L26 assembles in the nucleus (54,55). Here, we show that functional GFP-tagged L26 proteins accumulate in the nucleus upon inhibition of nucleocytoplasmic export of pre-60S r-particles by overexpression of the dominant-negative Nmd3⌬100 protein.…”
Section: Figmentioning
confidence: 57%
“…In contrast, the single rpl40a⌬ and specially the rpl40b⌬ mutant were clearly much more sensitive to this drug than the wild-type strain; the IC 50 value obtained for the rpl40a⌬ and rpl40b⌬ mutants was at least 10-fold lower than that of the wild-type strain. Interestingly, this sensitivity is not simply related to a lower dosage of an r-protein because the IC 50 value of an rpl35b⌬ mutant is practically identical to that of the wild-type strain. Moreover, the effect of sordarin seems to be very specific because we could not have observed enhanced sensitivity or resistance to other translation antibiotics (anisomycin, cycloheximide, hygromycin B, paromomycin, and neomycin) for the above strains when compared with their isogenic wild-type counterpart.…”
Section: Expression Of Ha-l40a Leads To Sordarin Resistance Whereas mentioning
confidence: 99%
“…One of the current challenges of the ribosome biogenesis field is defining the course of the assembly of r-proteins at a satisfactorily high resolution. A rough picture of this pathway has been obtained by pioneer work in yeast and HeLa cells (49,50). These studies indicate that most r-proteins are incorporated into nuclear pre-ribosomal particles either early or late in the process.…”
mentioning
confidence: 99%